Li4(NH2)3Cl amide-chloride: A new synthesis route, and hydrogen storage kinetic and thermodynamic properties - Gamba, Nadia Soledad (2016)
Amide-halide compounds were identified as possible promoters of the dehydrogenation kinetics of the Li-N-H system. However, reversible hydrogen storage capacities and sorption kinetics of Li4(NH2)3Cl and Li3Mg0.5(NH2)3Cl have not been reported yet. In the present work, Li4(NH2)3Cl was synthesized using a new synthesis route that involves the pre-milling of a LiNH2-LiCl mixture. Attempts to synthesize Li3Mg0.5(NH2)3Cl by applying similar synthesis procedures using LiNH2 and 0.5MgCl2 were unsuccessful; instead, a mixture of Li4(NH2)3Cl-0.5Mg(NH2)2 was obtained. The hydrogen storage properties of the Li4(NH2)3Cl-3LiH and Li4(NH2)3Cl-0.5Mg(NH2)2-3LiH composites were evaluated between 200 °C and 300 °C. The onset of hydrogen release was reduced by 20 °C when Li4(NH2)3Cl-3LiH decomposed in the presence of Mg(NH2)2 (180 °C with respect to 200 °C) and its hydrogen desorption rate increased by 83%. However, no change in the dehydrogenation activation energy was observed for Li4(NH2)3Cl-3LiH decomposition due to minor amounts of Mg(NH2)2. The hydrogen storage capacity under cycling was reduced from about 3.0 wt% to 1.5 wt% at 300 °C, after rehydrogenation at 6.0 MPa. The formation of Li7(NH)3Cl was clearly identified in the dehydrogenated material. Unfortunately, the sloped plateau and the thermodynamic stability of Li4(NH2)3Cl-3LiH precludes its hydrogen storage applicability.